Phonological process in Japanese loanwords Gairaigo and Wasei Eigo - Astariani, Putu Sandra Putri; Suciani, Ni Ketut; Sitawati, Anak Agung Raka (Journal of Applied Studies in Language, 2024)
This study delves into phonological processes and changes in two distinct categories of loanwords in Japanese: gairaigo (foreign loanwords) and wasei eigo (Japanese-coined English words). Gairaigo are borrowings from foreign languages, predominantly English, while wasei eigo refers to words created within the Japanese language using English morphemes. The phonological adaptation of these loanwords undergoes various processes, e.g., assimilation, syllable structure, attenuation and strengthening, and neutralization. These processes are reflecting the dynamic nature of language contact and cultural exchange. In the case of gairaigo, phonological processes often involve the adaptation of sounds to conform to Japanese phonotactics and speech patterns. This may include the simplification or substitution of consonant clusters, vowel lengthening or shortening, and the incorporation of pitch accent patterns native to Japanese. Wasei eigo, on the other hand, undergoes phonological changes rooted in the native Japanese phonological system. Despite being constructed with English morphemes, wasei eigo words often exhibit phonetic features characteristic of Japanese. Moreover, these words may evolve over time through processes of sound change and assimilation, reflecting shifts in linguistic preferences and cultural influences. Overall, the phonological adaptation of gairaigo and wasei eigo showcases the linguistic borrowing, cultural assimilation, and the phonological systems of both source and target languages. Understanding these processes provides insights into the dynamic nature of language contact and the evolution of linguistic diversity in Japanese society.